Chenopodium pumilio R. BR. (Chenopodiaceae), novedad corológica para Andalucía Oriental (España). Chenopodium pumilio R. Br. (Chenopodiaceae), new record for eastern Andalusia (Spain) - López Tirado, Javier (Acta Botanica Malacitana, 2013)
Chenopodium pumilio R. Br. (Chenopodiaceae), new record for eastern Andalusia (Spain) Palabras clave. Corología, Chenopodium pumilio, Andalucía oriental. Key words. Chorology, Chenopodium pumilio, eastern Andalusia.